Reconstruction of Araucaria araucana cone production reveals warming intensifies regionally synchronized masting - Andrew Hacket‐Pain; Fidel A. Roig; Davide Ascoli; Carlos LeQuesne; Martin Hadad (Ecosphere)
Abstract The reproduction of many long‐lived plants is highly variable and synchronized, known as masting. Masting is a key driver of plant regeneration dynamics and has cascading effects on food webs and carbon and nutrient fluxes through ecosystems. Masting patterns can respond to changes in climate, but natural long‐term variability in masting behavior (i.e., baseline variability) is poorly understood. Here we use tree‐rings to create a four‐century reconstruction of annual cone production to uncover centennial‐scale evolution in masting of Araucaria araucana, a dioecious masting species in South America. Over the last four decades, direct observations of annual cone production in this species revealed remarkable range‐wide synchrony of masting. Our tree‐ring‐based reconstruction places this in a long‐term context, revealing that intense regional masting is not a consistent feature of A. araucana reproduction. For extensive periods over the last four centuries, masting has been a site‐specific phenomenon, with variability in cone production that was not regionally synchronized. Comparison with regional climate reconstructions indicates that regional synchrony of masting varies with regional temperature trends, including during recent decades. During warmer periods, synchrony is enhanced, and during cooler periods, regional synchrony breaks down. These dynamics have implications for understanding the reproduction of this iconic and endangered tree species and provide evidence of long‐term linkages between climate change and masting behavior. Our study demonstrates the potential for novel tree‐ring‐based reconstructions of masting to reveal crucial insights into baseline variability and the response of masting to climate change.